The burden of acute pain in the U.S. in the wake of the opioid crisis - Hackworth, James C.; Schneider, John E.; Do Valle, Maggie; Fam, David; Argoff, Charles; Offidani, Emanuela; Potenziano, Jim (Frontiers in Pain Research, 2025)
The prevalence of acute pain has grown substantially over the past two decades, due primarily to more surgeries, an aging population, and the rapid growth in the prevalence of metabolic disease. Although opioids are often the only effective treatment for many types of acute pain, especially severe acute pain, their use, even over a short period of time, comes with substantial risks of dependence, misuse, and diversion. Moreover, a large fraction of the patients currently suffering from opioid use disorder and those dying from opioid overdoses had their first exposure as pain patients. Conversely, refraining from using opioids in cases where other treatment options are ineffective creates a different set of risks. This potential undertreatment of acute pain, especially severe acute pain, increases the risk of acute pain transitioning to chronic pain. The use of opioids to treat acute pain and the ineffective treatment of acute pain have important implications for population health and health care costs.